ETIKA PENELITIAN DAN PARTISIPASI ANAK DALAM KEGIATAN PENELITIAN (Research Ethics and the Participation of Children on Research Activities ) - Yanuar Farida Wismayanti (Politeknik Kesejahteraan Sosial, 2005)
Child participation is the biggest issue on child rights implementation on research activities. Most researches have exclusively given high attention for adult to be treated as participants. of respondents. However, child participahon on research has been as a key succes for participantsÂ research. Henceforth, there 1s a general opinion that child participation may contribute greatly for the development process. Thus, participatory research which considers the involvement of children would be able that research to receive a comprehensive data and information of particular issues